BEHÇET HASTALARINDA KONJONKTİVAL FLORA DEĞİŞİKLİKLERİ - GÜNDÜZ, AYTEN (Fırat Üniveristesi, 2007)
Behçet Hastalarında Konjoktival Flora DeğişiklikleriBehçet hastalarının konjonktival florasının normal popülasyonuna göredeğişikliklerini saptamayı amaçladık.Bu çalışma inaktif periyotta olan 50 Behçet hastasından oluşan çalışma grubuile ( 11-76 yaş arası, 32 erkek, 18 bayan) sistemik ve oküler başka hastalığıolmayan, sağlıklı, yaş ve cins açısından çalışma grubu ile uyumlu 50 olgudanoluşan kontrol grubunu (11-74 yaş arası, 31 erkek, 19 bayan) kapsamaktadır.Hastaların yaş ortalamaları Behçet grubunda 36.04Â±2.16, kontrol grubunda35.64Â±1.96 idi. Kültür için steril eküvyonla alt konjonktival forniksten sürüntüalınıp, kanlı, Eosine Methylene Blue (EMB), çukulatamsı ve SabouraudDekstroz Agar besiyerlerine ekim yapıldı.Behçet grubunun %92'sinde (n=46) ve kontrol grubunun %56'sında (n=29)bakteriyel üreme gözlendi. Behçet hastalarının 12'sinde (%24) Staphylococcusaureus, 32'sinde (%64) koagülaz negatif stafilokok (KNS), 8'inde (%16)Moraxella spp., 8'inde (%16) Streptococcus spp. 4'ünde (%8) Bacillus spp.,4'ünde (%8) Neisseria spp., 3'ünde (%6) Candida spp. ve 1'inde (%2)Haemophilus spp. üremesi saptandı. Kontrol grubundaki olguların 2'sinde (%4)S. aureus, 24'ünde (%48) KNS, 2'sinde (%4) Moraxella spp, 1'inde (%2)Streptococcus spp, 3'ünde (%6) Bacillus spp, 3'ünde (%6) Neisseria spp ve1'inde (%2) Candida spp üredi. Kontrol grubunda Haemophilus spp üremedi.Behçet grubunda spp ve sppS. aureus, Moraxella Streptococcuskolonizasyonları kontrol grubuna göre anlamlı olarak yüksek saptandı (p<0.05).Bu nedenle göz içi cerrahi uygulanacak Behçet hastalarında özellikle S.aureus'a bağlı ameliyat sonrası endoftalmilerden korunmak için profilaktiktedavilerin yapılmasının uygun olacağını düşünüyoruz.Anahtar Kelimeler: Behçet Hastalığı, Konjonktival Flora,Göz Enfeksiyonu.

Conjunctival Flora Alteration in the Patients with Behcet?s Diseaseİn this study, it was aimed to determine the differentation of conjunctivalflora in the patients with Behcet?s Disease regarding to normal population.Fifty Behcet patients (age range 11-76, 32 man and 18 women) in inactiveperiod as a study group and 50 healthy persons (age range 11-74, 31 man and19 women) as a control group, who did not have any ocular and systemicdisease and were age and sexually consistent with study group, were includedin to the study. The average age of the Behcet patients was 36.04Â±2.16 and ofthe control group patients was 35.64Â±1.96. Swab cultures were taken from thelower conjunctival fornix and were inoculated to blood, Eosine-Methylene Blue(EMB), chocolate and sabouraud dextrose agar mediums.Bacterial growth was observed in 92% (n=46) of the Behcet group and 56%(n=29) of the control group. Of the Behcet patients, Staphylococcus aureusgrew in 12 (24%) samples, coagulase negative staphylococci (CoNS) grew in32 (64%), Moraxella spp. grew in 8 (16%), Streptococcus spp grew in 8 (16%),Bacillus spp. grew in 4 (8%), Neisseria spp. grew in 4 (8%), Candida spp. grewin 3 (6%) and Haemophilus spp. grew in 1 (2%) samples. Of the control group,S. aureus grew in 2 (4%) samples, CoNS grew in 24 (48%), Moraxella spp.Grew in 2 (4%), Streptococcus spp. grew in 1 (2%), Bacillus spp. grew in 3(6%), Neisseria spp. grew in 1 (2%) and Candida spp. grew in 1 (2%) samples.Haemophilus did not grow in control group.Colonization of S. aureus, Moraxella spp. and Streptococcus spp. in Behcetpatients was determined significantly higher (p<0.05) regarding to the controlgroup. Therefore, we suggest that particularly S. aureus should be consideredwhile managing therapy for Behcet patients whom will receive eye surgery orwhom having external eye infection.Key-words: Behcet?s Disease, Conjunctival Flora, Eye İnfection.
Conjunctival flora alteration in the patients with behcet's disease
Keywords: Mikrobiyoloji